Science of beauty face value - Crisp, Mary.; Stone, Sharon; Hewes, Jonathan; Phillips, Katrina; Johnson, Fiona Scott; Cane, Georgann; Discovery Channel (Firm). ([Bethesda, Md.] Discovery Communications, 2007)
In this program, researchers are for the first time cracking the code of beauty using the science of evolutionary biology and psychology.
Produced by Wall to Wall Television for TLC.
Distributed in the Philippines through MagnaVision.
Executive producer, Jonathan Hewes ; series producer, Katrina Phillips ; assistant producer, Fiona Scott-Johnson ; writer, Georgann Cane ; narrator, Sharon Stone.
Keywords: Face; Face perception; Aesthetics; Interpersonal attraction; Beauty, Personal